Prevalence of hypertension and its associated risk factors among bank employees in Chidambaram: a cross sectional study - S., Rajkumar; I. K., Annie; Felix A., John William (International Journal Of Community Medicine And Public Health, 2022)
Background: The job nature of a bank employee is both sedentary and stressful. High level of mental stress places them at a higher risk of developing non communicable diseases like diabetes and hypertension. Aim of the study was to assess the prevalence of hypertension and its associated risk factors among bank employees. Methods: A descriptive cross-sectional study was conducted among 265 bank employees using a semi structured questionnaire. Risk factors like extra salt intake, lifestyle factors like smoking, alcohol, physical activity were taken into account. Results: The mean age of the participants was 36.93±8.657. The prevalence of hypertension was found to be 19.5% (52) out of which 5.2% (14) were known cases of hypertension. A significant association was found between extra salt intake, smoking, alcohol and hypertension. Conclusions: The prevalence of hypertension among bank employees in Chidambaram is low compared to the studies among bank employees in other parts of the country. Extra salt intake, smoking, alcohol and stress levels were found to be the significant factors associated with hypertension.